Security in focus: An empirical examination of perceived security’s impact on tam-based use behavior of e-wallets - Jasmine Vivienne Andrew; Sylvia Nabila Azwa Ambad; Nelson Lajuni; Christine Jacqueline Runggol; Karen Esther Tan (Human Resource Management Academic Research Society (HRMARS), 2025)
The present study investigates factors influencing the behavioural use of e-wallet among youths in Malaysia. It is necessary for fintech practitioners and policymakers to look into the factors that drive young users to adopt e-wallet given the rapid growth in Malaysia’s digital financial services. This study is fuelled by the need to bridge the gap between user trust and e-wallet use, especially among security-conscious and technology savvy youths. Thus, the study aims to assess the effect of perceived usefulness and perceived ease of use in the Technology Acceptance Model (TAM) on youths’ e-wallet behavioural use by extending it with perceived security. An online survey was conducted with 150 questionnaires distributed to youths around Malaysia. The data was then analysed using the Partial Least Square-Structural Equation Modelling (PLS-SEM) software. The findings revealed that perceived usefulness and perceived security have a significant positive effect on youths’ e-wallet use behaviour, while perceived ease of use shows an insignificant effect. The study adds to the expanding literature on security in financial technology, i.e., the e-wallet, by determining the perceived security’s role in e-wallet use behaviour. The outcome of this study would benefit policymakers, e-wallet providers, and academics in undertaking strategies that would enhance perceived security and encourage users’ use behaviour.